Digital Literacy Challenges Among English Education Students at Muhammadiyah University of Sidenreng Rappang - Nurul Indah Roma; Sam Hermansyah; Isumarni (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to identify the specific issues related to digital literacy and the components that impact digital literacy faced by first-semester students majoring in English Education. This research uses qualitative methods. Findings from this study show that Socially Responsible is a component that has a higher impact on digital literacy, and constructive is a lower component that has an impact on digital literacy. So, it shows that socially responsible students are already aware of digital literacy, but constructive students are still confused about creating and sharing good digital content. Some of the digital problems found by first-semester students of the English education department are problems such as unclear sounds when studying online and internet connection problems, which hinder their understanding of the material being taught. Although students are aware of the benefits of digital technology, they face significant difficulties in using the internet, as well as challenges in the transition period from high school to university that uses more technology and there is a need for greater support from educational institutions to improve their digital literacy.